PENGARUH SISTEM INFORMASI PEROLEHAN DAN PENYUSUTAN AKTIVA TETAP BERBASIS WEB DI PT. HASIL DAMAI TEXTILE BANDUNG - Agustin, Cahyadi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
This study aims to create a design of information systems the acquisition and depreciation of web-based fixed assets using php mysql database at PT. Hasil Damai Textile Bandung. Software development method using waterfall. From the research conducted, it was found the problem that the process of recording and calculating depreciation of fixed assets still uses Microsoft excel so it requires a relatively long time and the calculation results are less accurate, and data storage is less secure and irregular so it is difficult to identify fixed assets that will expire depreciation.